Seismic Evaluation and Pla sti c Hinge Analysis for Metro Piers - Viraj Shrikhande, Jagruti Patil, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2022)
In general the most suitable choices for improvement of India is prone to severe earthquakes in the last century. More than 50 % area in the country is considered critical to damaging earthquakes. There is a country vide attention to the seismic behavior of existing buildings comparatively existing bridges have less. However, bridges are extensively important components of the transportation sector in any country. According to antiquated building rules, the bulk of Indian bridges were insufficiently designed to withstand seismic and wind pressures. For short piers, the design shear capacities (With an aspect ratio of two to three) is discovered that is should be lesser than the comparable under flexural shear demand overstrength conditions. There is a lot of literature capable of designing and analyzing the piers. Nonetheless, the discussion and study regarding an arrangement and seismic performance of double-decker bridge metro pier are not done, a seismic load is applied to a pier 20m height situated in the zone III. Later the process of analysis is completed employing STAAD software. An Axial forces, bending moment, shear force, time period, and the storey displacements are calculated, also the location of plastic hinge formation is computed.